2008
DOI: 10.1002/chin.200833036
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis and QSAR Studies of Thiosemicarbazides, 1,2,4‐Triazoles, 1,3,4‐Thiadiazoles and 1,3,4‐Oxadiazoles Derivatives as Potential Antibacterial Agents.

Abstract: Ring closure reactions O 0130Synthesis and QSAR Studies of Thiosemicarbazides, 1,2,4-Triazoles, 1,3,4-Thiadiazoles and 1,3,4-Oxadiazoles Derivatives as Potential Antibacterial Agents. -A series of title compounds of type (I)-(V) is prepared and screened for antibacterial activities. The results are discussed on the basis of QSAR calculations. -(DESAI*, N. C.; BHAVSAR, A. M.; SHAH, M. D.; SAXENA, A. K.; Indian J. Chem., Sect. B: Org. Chem. Incl. Med. Chem. 47 (2008) 4, 579-585; Med. Chem. Div., Dep. Chem., Bhav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The study reported in this article is in continuation of the previous work aimed at synthesizing bio-active heterocyclic entities (Desai and Desai, 2005;Desai and Undavia, 1998;Desai and Undavia, 1996;Desai and Bhavsar, 2008;Desai and Saxena, 2008;Desai and Baldaniya, 2009). …”
Section: Introductionmentioning
confidence: 76%
“…The study reported in this article is in continuation of the previous work aimed at synthesizing bio-active heterocyclic entities (Desai and Desai, 2005;Desai and Undavia, 1998;Desai and Undavia, 1996;Desai and Bhavsar, 2008;Desai and Saxena, 2008;Desai and Baldaniya, 2009). …”
Section: Introductionmentioning
confidence: 76%
“…A mixture of compound (1) (0.01 mole) and (0.02 mole) of phenyl isothiocyanate in ethanol absolute was heated under reflux. After 1hr the reaction mixture was cooled and the solid product was collected and recrystallized from ethanol [6,7].…”
Section: Preparation Of N-phenyl-2-(2-(3-phenyl Thioureido)benzoyl) Hmentioning
confidence: 99%
“…H 2 SO 4 and stirred for 1hr then poured onto crushed ice. The resulting solid was recrystallized from ethanol [6,7].…”
Section: Preparation Of 1-phenyl -3-(2-(5-(phenyl Amino)-1 3 4-thiamentioning
confidence: 99%
See 2 more Smart Citations